Cafe an industrial-strength algebraic formal method - Futatsugi, Kokichi; Tamai, T. (Tetsuo); Nakagawa, A. T. (Ataru T.) (Amsterdam ; New York : Elsevier, 2000)
This book contains selected papers on the language, applications, and environments of CafeOBJ, which is a state-of -the-art algebraic specification language. The authors are speakers at a workshop held in 1998 to commemorate a large industrial/academic project dedicated to CafeOBJ. The project involved more than 40 people from more than 10 organisations, of which 6 are industrial. The workshop attracted about 30 talks and more than 70 attendees. The papers in the book however, are either heavily revised versions presented at the workshop, to reflect recent advancements or research; or completely new ones, written especially for this book. In this regard, the book is not a usual postpublication after a workshop. Also, although it is a compendium of papers that are related to CafeOBJ, the book is not a manual, reference, or tutorial of CafeOBJ. Probably the best description is that it is a collection of papers that investigate how to use, or to make it easy to use, CafeOBJ. Reflecting the diverse nature of the project and its participants (most of the authors are participants to the project), the papers, put together, offer a comprehensive picture from this methodological perspective. Some papers deal with various advanced aspects of the language, such as rewriting logic and behavioural logic. For rewriting logic, a couple of significant applications were reported. In particular, UML, now considered de facto standard language for modelling systems, is the subject of one paper. For behavioural logic, new methodological guidelines are presented. Some papers shed new light on a more traditional paradigm in the language; order-sorted equational specifications. One paper, in particular, deal with a way to associate CafeOBJ with object-oriented programming. The other papers deal with environments for writing and vertifying specifications written in CafeOBJ. Underlying those papers are two major considerations: user interfaces for manipulating specifications, and systematic supports for proofs. All the environments explained in the papers assume and support distributed computing, and de facto standard network technologies, such as WWW and http, are incorporated.
Building equational proving tools by reflection in rewriting logic / M. Clavel, F. Durβan, S. Eker and J. Meseguer -- CafeOBJ jewels / Rzvan Diaconescu, Kokichi Futatsugi and Shusaku Iida -- An overview of the Tatami project / Joseph Goguen, Kai Lin, Grigore Roπsu, Akira Mori and Bogdan Warinschi -- Proof assistance for equational specifications based on proof obligations / Masaki Ishiguro and Ataru T. Nakagawa -- Generating rewrite theories from UML collaborations / Alexander Knapp -- Casl for CafeOBJ users / Peter D. Mosses -- CafePie : a visual programming system for CafeOBJ / Tohru Ogawa and Jiro Tanaka -- On extracting algebraic specifications from untyped object-oriented programs / Hirotaka Ohkubo, Toshiki Sakabe and Yasuyoshi Inagaki -- An environment for systematic development of algebraic specifications on networks / Akishi Seo and Ataru T. Nakagawa.
Selected papers from a symposium held in Numazu, April 1998.
Includes bibliographical references.
Keywords: Algebraic logic -- Congresses; Formal methods (Computer science) -- Congresses; Electronic books; Conference proceedings